The Uniqueness of Megeret Pandan Tradition as Tourist Attraction in Tenganan Village, Karangasem, Bali - Anak Agung Istri Putera Widiastiti; Anak Agung Istri Ngurah Dyah Prami (Journal of Business on Hospitality and Tourism, 2021)
Megeret Pandan or mekare-kare is a tradition in Tenganan Village, Karangasem. This tradition is related to local ritual activities and beliefs in which all men from children to adults take turn performing in an arena to play dexterity match as fighters by using pandan leaves, a shield from rattan wicker and traditional costume. This tradition is potential to be tourist attraction since the tourists are welcome to participate. The purpose of this study is to determine the existence the tradition of Megeret Pandan as a tourist attraction in Tenganan Village and its relation to the defense of ancestral heritage. This study used qualitative method and it was conducted through inductive process. The theory was Structural Functional Theory of Talcott Parson concerning action system, in which the objective conditions were united with collective commitment upon certain value for the development of a social action form. Based on the research finding, it was concluded that the tradition of Megeret Pandan which was packaged in such a way as tourist attraction could be tourist attraction without leaving the sacred values within.